Altered sulcogyral patterns of orbitofrontal cortex in a large cohort of patients with schizophrenia - Shuichi Isomura (Nature Portfolio, 2017)
Abstract Abnormalities in prenatal brain development contribute to schizophrenia vulnerability. Orbitofrontal cortex sulcogyral patterns are largely determined during prenatal development, and four types of orbitofrontal cortex sulcogyral patterns have been classified in humans. Altered orbitofrontal cortex patterns have been reported in individuals with schizophrenia using magnetic resonance imaging; however, sample sizes of previous studies were small–medium effects for detection, and gender manifestation for orbitofrontal cortex sulcogyral patterns is unclear. The present study investigated orbitofrontal cortex patterns of 155 patients with schizophrenia and 375 healthy subjects. The orbitofrontal cortex sulcogyral pattern distributions of schizophrenia were significantly different compared with healthy subjects in the left hemisphere (χ 2 = 14.55, p = 0.002). In female schizophrenia, post-hoc analyses revealed significantly decreased Type I expression (χ 2 = 6.76, p = 0.009) and increased Type II expression (χ 2 = 11.56, p = 0.001) in the left hemisphere. The present study suggested that female schizophrenia showed altered orbitofrontal cortex patterns in the left hemisphere, which may be related to neurodevelopmental abnormality.